2013
DOI: 10.4161/hv.25076
|View full text |Cite
|
Sign up to set email alerts
|

Reactogenicity and safety of a liquid human rotavirus vaccine (RIX4414) in healthy adults, children and infants in China

Abstract: We report the findings of three randomized, double-blind, placebo-controlled Phase I studies undertaken to support licensure of the liquid formulation of the human G1P[8] rotavirus (RV) vaccine (RIX4414; GlaxoSmithKline Biologicals SA) in China. Healthy adults aged 18–45 y (n = 48) and children aged 2–6 y (n = 50) received a single dose of the human RV vaccine or placebo. Healthy infants (n = 50) aged 6–16 weeks at the time of first vaccination received two oral doses of the human RV vaccine or placebo accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
(11 reference statements)
0
15
0
Order By: Relevance
“…In the previously published version of this review there were 41 included studies. The review now includes 55 independent trials (see Characteristics of included studies), 14 of which are new to this update (RV1 Colgate 2016‐BGD; RV1 Kim 2012‐KOR; RV1 Li 2013a‐CHN; RV1 Li 2013b‐CHN; RV1 Li 2014‐CHN; RV1 NCT00158756‐RUS; RV1 Zaman 2017‐BGD; RV5 Dhingra 2014‐IND; RV5 Levin 2017‐AF; RV5 Mo 2017‐CHN; VAC Bhandari 2006‐IND; VAC Bhandari 2009‐IND; VAC Bhandari 2014‐IND; VAC Chandola 2017‐IND) and we also added another 23 new companion papers to previously included trials with this update. The review also includes 15 ongoing studies (see Characteristics of ongoing studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previously published version of this review there were 41 included studies. The review now includes 55 independent trials (see Characteristics of included studies), 14 of which are new to this update (RV1 Colgate 2016‐BGD; RV1 Kim 2012‐KOR; RV1 Li 2013a‐CHN; RV1 Li 2013b‐CHN; RV1 Li 2014‐CHN; RV1 NCT00158756‐RUS; RV1 Zaman 2017‐BGD; RV5 Dhingra 2014‐IND; RV5 Levin 2017‐AF; RV5 Mo 2017‐CHN; VAC Bhandari 2006‐IND; VAC Bhandari 2009‐IND; VAC Bhandari 2014‐IND; VAC Chandola 2017‐IND) and we also added another 23 new companion papers to previously included trials with this update. The review also includes 15 ongoing studies (see Characteristics of ongoing studies).…”
Section: Resultsmentioning
confidence: 99%
“…Most trials included healthy infants. Two trials included HIV‐infected or ‐exposed infants (RV1 Madhi 2010‐AF; RV1 Steele 2010a‐ZAF), one trial included premature infants (RV1 Omenaca 2012‐EU), and one trial included children aged two to six years (RV1 Li 2013a‐CHN).…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that the efficacy rate of vaccine against the G1 wild-type was 81%-82%, against the pooled non-G1 strain was 78%, against the non-G1P [8] strain was 81%, against hospitalization with severe diarrhea was 83%, and against hospitalization with any cause was 39%. [71] The vaccine has also been tested in China and Hong Kong, [54,55] with an efficacy rate of 87%-96% against hospitalization…”
Section: Monovalent Human G1 Rotavirus Vaccinementioning
confidence: 99%
“…[47] The efficacy of major human rotavirus vaccines in different settings is shown in the Table. [36,[47][48][49][50][51][52][53][54][55][56][57][58][59] Trials [47,60,61] showed that the efficacy of RotaTeq on diarrheal diseases and severe gastroenteritis was 74% and 98%, respectively. RotaTeq was also effective in combating each of the common circulating serotypes.…”
Section: Human-bovine Rotavirus Reassortant Vaccinementioning
confidence: 99%
See 1 more Smart Citation